Supplementing Maturation Medium With Insulin Growth Factor I and Vitrification-Warming Solutions With Reduced Glutathione Enhances Survival Rates and Development Ability of in vitro Matured Vitrified-Warmed Pig Oocytes - Pereira, Barbara Azevedo; Zangeronimo, Marcio Gilberto; Castillo-Martín, Miriam; Gadani, Beatrice; Chaves, Bruna Resende; Rodríguez-Gil, Joan Enric; Bonet, Sergi; Yeste, Marc (Frontiers in Physiology, 2019)
The present study sought to determine whether in vitro maturation (IVM) of pig oocytes in a medium supplemented with insulin growth factor-I (IGF-I) and subsequent vitrification with or without reduced glutathione (GSH) affect their quality and developmental competence, and the expression of genes involved in antioxidant, apoptotic and stress responses. In Experiment 1, cumulus-oocyte complexes were matured in the absence or presence of IGF-I (100ng·mL-1) and then vitrified-warmed with or without 2mM of GSH. Maturation rate was evaluated before vitrification, and oocyte viability, DNA fragmentation and relative transcript abundances of BCL-2-associated X protein (BAX), BCL2-like1 (BCL2L1), heat shock protein 70 (HSPA1A), glutathione peroxidase 1 (GPX1) and superoxide dismutase 1 (SOD1) genes were assessed in fresh and vitrified-warmed oocytes. In Experiment 2, fresh and vitrified-warmed oocytes were in vitro fertilized and their developmental competence determined. Whereas the addition of IGF-I to maturation medium had no effect on oocyte maturation, there was an increase in the survival rate of vitrified-warmed oocytes. This effect was accompanied with a concomitant augment in the relative transcript abundance of HSPA1A and a decrease of BAX. Furthermore, the addition of GSH to vitrification-warming media increased survival rates at post-warming. Likewise, the action of GSH was concomitant with an increase in the relative transcript abundance of GPX1 and a decrease of BAX. Blastocyst rates of vitrified-warmed oocytes did not differ from their fresh counterparts when IGF-I and GSH were combined. In conclusion, supplementing maturation medium with 100ng·mL-1 IGF-I and vitrification-warming solutions with 2mM GSH improves the quality and cryotolerance of IVM pig oocytes, through a mechanism that involves BAX, GPX1 and HSPA1A expression.